Comparison of Del Nido and histidine-tryptophan-ketoglutarate cardioplegia solutions: an animal study with prolonged ischaemia - Hoyer, Alexandro; Dieterlen, Maja-Theresa; Kang, Jagdip; Oetzel, Hanna; Wiesner, Karoline; Klaeske, Kristin; Kiefer, Philipp; Oßmann, Susann; Ginther, André; Kostelka, Martin; de Waha, Suzanne; Borger, Michael A. (Frontiers in Cardiovascular Medicine, 2024)
ObjectiveMyocardial protection is important for a successful procedure cardiac surgery, and the key element of myocardial protection is cardioplegia. We compared Del Nido cardioplegia (DN) and Bretschneider histidine-tryptophan-ketoglutarate cardioplegia (HTK) regarding cardioprotective effects in a porcine model of prolonged ischaemia.MethodsLandrace pigs weighing 50–60 kg were randomized to receive either DN (n = 9) or HTK (n = 9). All pigs underwent cardiac arrest for 90 min followed by 120 min of reperfusion/convalescence. A detailed set of laboratory, histological and functional parameters was acquired at baseline, during cardiac arrest and following reperfusion/convalescence.ResultsPressure-volume measurements revealed better systolic and diastolic left ventricular performance in DN as compared to HTK (both p < 0.05). Haemoglobin decreased after application of the cardioplegic solution. The decrease was more pronounced in the HTK group than in the DN group (p < 0.01). In contrast to DN, sodium (p < 0.01) and chloride levels (p < 0.05) were significantly decreased in the HTK group after initiation of CPB and remained decreased after reperfusion. The number of animals requiring defibrillations to restore sinus rhythm significantly differed between the groups [HTK: 100% (n = 9/9) vs. DN: 44.4% (n = 4/9), p = 0.03]. Expression of ICAM-1 as a marker of endothelial dysfunction was lower in the DN group compared to the HTK group (p = 0.02). Histological evaluation, oxidative and nitrosative stress, mitochondrial membrane integrity and apoptosis markers were comparable between DN and HTK groups (all p > 0.05).ConclusionsIn this porcine model with prolonged ischaemia, DN was superior to HTK in terms of haemoglobin levels, blood electrolytes, spontaneous return of sinus rhythm, left ventricular function, and endothelial injury. Histomorphological parameters indicative of ischaemia/reperfusion injury, oxidative stress and mitochondrial function as well as apoptosis-inducing factors did not differ.